Absence de captage de Crassostrea gigas dans le bassin de Marennes-Oléron en 1981 : causes et conséquences - Berthome, Jean-paul; Deslous-paoli, Jean-marc; Heral, Maurice; Razet, Daniel; Garnier, Jacqueline (Council Meeting, 1982, of the International Council for the Exploration of the Sea, (Copenhagen (Denmark)) (11 Oct 1982), 1982)
The want of C. gigas spat-catching in the Marennes-oleron basin in 1981 can be due to various different reasons which are analysed here. Physico -chemical and trophic factors that can induce variations in the quality of gametogenesis, are successively in comparison with the year 1979 when reproduction was good. The biochemical evolution and a study of gonads slow a lack in maturation in 1981 even during the summer period. Late maturation of gonads bring about physiological consequences which induced mortality of cultivated oysters at the end of winter. A feeble recruit and a decrease of the cultivated stock have economic consequences which here sketched up. Les différentes raisons possibles de l'absence de captage de C. gigas, en 1981 dans le bassin de Marennes-Oléron sont analysées par les auteurs. En comparaison avec l'année 1979, année de bonne reproduction, il est successivement présenté les facteurs physicochimiques et trophiques qui peuvent agir sur la gametogenèse. L'évolution biochimique et l'observation des gonades mettent en évidence un défaut de maturation, en 1981, même lors de la période estivale. Les conséquences physiologiques dues à cette maturation tardive des gonades ont entraîné à la fin de l'hiver des mortalités (30 %) sur les huîtres en élevage. Les conséquences économiques liées au faible recrutement et à la baisse du stock en élevage sont esquissées.